Polyimide slurry for flexible display substrate, preparation method of polyimide slurry and preparation method of polyimide film
Through specific monomer selection, proportional optimization and additive introduction, the problem of insufficient adhesion of polyimide film on the SiOx inorganic layer is solved, significantly improving adhesion and maintaining the overall performance of the film, and improving the reliability of flexible display equipment.
Patent Information
- Application Number
- CN202411937508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
The adhesion of the polyimide film on the SiOx inorganic layer is insufficient, resulting in a decrease in the reliability and service life of the flexible display panel.
Through specific monomer selection, proportion optimization, additive introduction and preparation process adjustment, the bonding interface energy between the polyimide slurry and the SiOx inorganic layer is improved, and the adhesion between the polyimide film and the SiOx inorganic layer is significantly enhanced.
It significantly improves the adhesion between the polyimide film and the SiOx inorganic layer, maintains the optical, mechanical and thermal properties of the film, and improves the reliability and durability of the flexible display equipment.
Smart Images

Figure CN119613720A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and specifically, it discloses a polyimide slurry for a flexible display substrate and a preparation method thereof, and a preparation method of a polyimide film. Background Art
[0002] With the rapid development of flexible display technology, the performance requirements for flexible display panels are increasing. Polyimide (PI) film has become an important component of flexible display panels due to its excellent thermal stability, chemical stability and mechanical properties. In the process, if the polyimide film is prepared directly on the SiOx inorganic layer, due to the influence of the interface energy and the low surface roughness of SiOx, the adhesion of the traditional polyimide film on the SiOx substrate is often insufficient, which will greatly reduce the reliability and service life of the flexible display panel.
[0003] Currently, the main method is to evaporate an a-Si layer on the SiOx inorganic layer and improve the adhesion between the polyimide and the SiOx inorganic layer through the bonding force between the intermediate a-Si layer and the polyimide. Although this process method improves the adhesion between the polyimide and the SiOx inorganic layer, it also increases the process cost of the panel and reduces the yield of the preparation process.
[0004] The main reasons why polyimide materials cannot directly form high adhesion films in SiOx inorganic layers can be summarized as follows:
[0005] 1. Chemical stability: Since polyimide has excellent chemical stability and shows good resistance to most chemical solvents and acid-base solutions, it makes it difficult for traditional adhesives to form stable chemical bonds with PI materials.
[0006] 2. High melting point and thermal stability: PI material has a high melting point and excellent thermal stability. During conventional bonding, the curing temperature of the adhesive often cannot reach the melting point of the PI material, making it difficult to achieve effective bonding.
[0007] 3. Low surface energy: The surface energy of PI material is low and difficult to be wetted, which affects the interaction with the adhesive, resulting in the adhesive being unable to effectively penetrate the surface of the PI material, reducing the bonding strength.
[0008] 4. Crystallinity and orientation: PI materials may exhibit crystallinity and orientation, resulting in surface unevenness and defects, increasing the difficulty of bonding.
[0009] 5. Thermal expansion coefficient and mechanical strength: In the microelectronics industry, PI films have the problem of reducing the thermal expansion coefficient and mechanical strength at the same time, which may cause stress mismatch between materials and affect the bonding effect.
[0010] 6. Chemical bonding between polyimide and SiOx inorganic layer: Because the surface of SiOx is mostly Si-O-Si structure, and most of it is hydrophobic structure, it cannot mutually infiltrate with polyamic acid containing carboxyl (COOH) hydrophilic structure, and it also cannot form hydrogen bonds with carbonyl (C=O) after imidization, resulting in decreased adhesion.
[0011] 7. Influence of film-making process conditions: Since the slurry is coated on the surface of the substrate and dried to a dry film at a certain wet film thickness, if the process conditions are not matched, the film layer will have a large residual internal stress, which will easily lead to a decrease in adhesion.
[0012] Therefore, it is particularly important to develop a polyimide slurry and a method for preparing the film that can directly improve the adhesion with the SiOx inorganic layer. Summary of the invention
[0013] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a polyimide slurry and a film, which significantly improves the bonding interface energy between the two through specific monomer selection, ratio optimization, introduction of additives and adjustment of the preparation process. This method can significantly enhance the adhesion between the polyimide film and the SiOx inorganic layer while maintaining the optical and mechanical properties and thermal properties of the film, so as to improve the reliability and durability of the flexible display device.
[0014] The technical solution is as follows:
[0015] In one aspect, the present invention provides a polyimide slurry for a flexible display substrate, wherein the raw materials for preparing the polyimide slurry include diamine, dianhydride, a capping agent, a solvent and an additive;
[0016] The diamine comprises a main monomer and an auxiliary monomer, the main monomer is a diamine monomer containing a carboxyl group, and the molar percentage of the main monomer to the diamine is not more than 30%;
[0017] The additives include additive A and additive B added in batches, the amount of additive A added is 1-3% of the molar amount of diamine, and the amount of additive B added is 5-50 ppm of the total solution mass;
[0018] The amount of the end-capping agent added is 0.5-2% of the molar amount of the diamine.
[0019] Wherein, the main monomer in the diamine is 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid.
[0020] Furthermore, the auxiliary monomer in the diamine is selected from one or more combinations of p-phenylenediamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4-diaminobenzanilide, 4,4'-diaminodicyclohexylmethane, 9,9'-bis(4-amino-phenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 4,4'-diaminodiphenylmethane, 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline], and 4,4-bis(3-aminophenoxy)biphenyl.
[0021] The dianhydride is selected from one or more combinations of 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, 4,4-hexafluoroisopropylphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, and bisphenol A diether dianhydride.
[0022] The end-capping agent is selected from one or more combinations of maleic anhydride, 4-phenylethynylphthalic anhydride, phthalic anhydride, 4-(phenylethynyl)aniline, 4-aminoacetophenone, 3,3',4,4'-biphenyltetracarboxylic acid, and pyromellitic acid.
[0023] The additive A is selected from one or more combinations of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and 3-methacryloyloxypropylmethyldimethoxysilane; and the additive B is selected from benzaldehyde.
[0024] Furthermore, the amount of the end-capping agent added is preferably 0.5 to 1% of the molar amount of the diamine.
[0025] Furthermore, the amount of the additive A added is preferably 1.5-2.5% of the molar amount of the diamine, and the amount of the additive B added is preferably 25 ppm of the total solution mass.
[0026] On the other hand, the present invention also provides a method for preparing the polyimide slurry for the flexible display substrate as described above, characterized in that it comprises the following steps:
[0027] S1, copolymerizing diamine and dianhydride to generate a polyamic acid solution;
[0028] S2, adjusting the amine anhydride molar ratio of the polyamic acid solution obtained in the above step to achieve a suitable viscosity and solid content;
[0029] S3, adding a specific proportion of the end-capping agent to the polyamic acid solution obtained in the above step;
[0030] S4, heating the polyamic acid solution obtained in the above step to a specific temperature, slowly adding a certain proportion of additives twice, and repeatedly stirring to ensure that the solution is evenly dispersed;
[0031] S5. Filter the above-mentioned solution after the polymerization through a filter element with a certain pore size to finally obtain a polyimide slurry.
[0032] In another aspect, the present invention further provides a method for preparing a polyimide film, characterized in that it comprises the following steps:
[0033] Providing a polyimide slurry prepared according to the above-mentioned preparation method;
[0034] Under room temperature, the coating speed is controlled to uniformly cast the polyimide slurry onto the SiOx substrate;
[0035] Using a reduced pressure drying device to dry and remove the solvent at low temperature to form a film;
[0036] The film is heated in a nitrogen environment for imidization to finally form a polyimide film.
[0037] The curing temperature and time can be optimized according to specific needs, but it is necessary to maintain a low heating rate below 200°C. For example, the heating rate at 80-200°C should be maintained at 2-3°C / min, and the constant temperature time at high temperature of 450°C must be maintained in the range of 25-40 minutes.
[0038] After curing, the polyimide film forms good adhesion with the SiOx substrate. A peeling device is needed to slowly peel the PI film from the SiOx substrate. The adhesion between the polyimide film and the substrate can also be measured during the peeling process. The peeled film maintains excellent mechanical / optical / thermal properties.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention introduces a diamine monomer containing a carboxyl group and a diamine monomer with a rigid structure, adopts a multi-polymerization method, controls the molecular weight by adding a partial end-capping agent, introduces an additive A to improve the interface energy of the SiOx inorganic layer, and introduces an additive B to ensure the comprehensive performance stability of the material, ensure the increase of the adhesion with the SiOx inorganic layer, and ensure that the comprehensive performance of the PI film material can meet the performance requirements of the flexible display; at the same time, the baking process is optimized, such as adjusting the heating rate in the low temperature stage, reducing the residual stress in the film, thereby enhancing the interface bonding of the SiOx inorganic layer and improving the adhesion.
[0041] 2. The present invention significantly improves the adhesion between the polyimide film and the SiOx inorganic layer through specific formula and process development, as well as optimization of the preparation process, effectively solving the problem of easy detachment of the traditional polyimide film and avoiding electrical performance failures when used in flexible display devices.
[0042] 3. The prepared polyimide film not only has good adhesion, but also maintains the excellent optical properties, mechanical properties and thermal properties of the polyimide film, and is suitable for high-performance flexible display technology.
[0043] 4. The film-making process of the polyimide substrate for the yellow light segment of the flexible display has been optimized, the a-Si process has been removed, the PI substrate film-making process has been simplified, a lot of costs have been saved, and the cycle time of the product has been shortened.
[0044] 5. The preparation method of the polyimide slurry and film provided by the present invention is simple and efficient, and can be widely used in the fields of flexible display panels, flexible electronic devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A simplified schematic diagram of a method for preparing polyimide slurry;
[0046] Figure 2 A simplified schematic diagram of the process for preparing polyimide film. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0049] The raw materials for preparing the polyimide slurry according to a specific embodiment of the present invention include diamine, dianhydride, end-capping agent, solvent and additives.
[0050] The diamine includes a main monomer and an auxiliary monomer. The main monomer is a diamine monomer containing a carboxyl group, preferably 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid (DADB). The molar percentage of the main monomer to the diamine is not more than 30%.
[0051] The auxiliary monomer is a conventional diamine monomer, and one or more of p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 4,4-diaminobenzanilide (DABA), 4,4'-diaminodicyclohexylmethane (HMDA), 9,9'-bis(4-amino-phenyl)fluorene (FDA), 9,9-bis(4-amino-3-fluorophenyl)fluorene (FFDA), 4,4'-diaminodiphenylmethane (MDA), 4,4'-[1,4-phenylbis(oxygen)]bis[3-(trifluoromethyl)aniline] (6FAPB), and 4,4-bis(3-aminophenoxy)biphenyl (BAPB-M) can be selected.
[0052] Among them, the dianhydride includes 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), 4,4-hexafluoroisopropylphthalic anhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (BODA), and bisphenol A diether dianhydride (BPADA).
[0053] The additives include additive A and additive B added in batches, the amount of additive A added is 1-3% of the molar amount of diamine, preferably 1.5-2.5%, and the amount of additive B added is 5-50ppm of the total solution mass, preferably 25ppm.
[0054] Additive A is a silane coupling agent, such as 3-aminopropyltriethoxysilane (KH550), 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560), 3-(methacryloyloxy)propyltrimethoxysilane (KH570), 3-methacryloyloxypropylmethyldimethoxysilane (KH572) or a combination thereof.
[0055] Additive B is benzaldehyde (Bz-CHO).
[0056] The amount of the end-capping agent added is 0.5-2% of the molar amount of the diamine, preferably 0.5-1%.
[0057] The end-capping agent is selected from maleic anhydride (MA), 4-phenylethynylphthalic anhydride (4-PEPA), phthalic anhydride (PA), 4-(phenylethynyl)aniline (PEPA), 4-aminoacetophenone (4-AAP), 3,3',4,4'-biphenyltetracarboxylic acid (BPTA), and pyromellitic acid (PMA).
[0058] Among them, the solvent is preferably N-methylpyrrolidone (NMP).
[0059] like Figure 1 The figure shows a simplified schematic diagram of a method for preparing polyimide slurry.
[0060] In a polymerization process using a normal addition sequence, one or more diamines are first dissolved in a solvent, and then one or more dianhydrides are gradually added to start the polymerization reaction. As polyamic acid is formed, the viscosity of the solution continues to increase. The initial temperature of the polymerization reaction is controlled between 0 and 5°C. After the reaction is carried out for 2 to 5 hours, the temperature is raised to room temperature 23 to 25°C and reacted for 2 hours. The amine anhydride molar ratio of the above polyamic acid solution is adjusted to achieve a suitable viscosity and solid content. The end-capping agent is added to the polyamic acid solution after the reaction and stirred for 2 hours, then the temperature is raised to 60°C, and additives A and additives B are added in batches, stirred for 2 hours, and filtered to obtain a light yellow polyimide slurry.
[0061] like Figure 2 As shown, it is a simplified schematic diagram of the process for preparing polyimide film.
[0062] A slit coating device is used to evenly coat the light yellow polyimide slurry on the SiOx inorganic layer substrate, and HVCD and high-temperature imidization baking are performed. The heating program usually contains multiple steps. The highest heating temperature is about 450°C. The constant temperature time needs to be maintained in the range of 25 to 40 minutes, and the heating rate below 200°C needs to be maintained at 2 to 3°C / min.
[0063] The prepared light yellow polyimide film was left to stand in a high humidity environment for 8 hours, and the PI film was slowly peeled off by a film peeling device to obtain a light yellow polyimide film.
[0064] The more detailed preparation steps are as follows:
[0065] 1) Under room temperature, the coating speed is controlled to uniformly cast the prepared polyimide slurry onto the SiOx substrate.
[0066] 2) Drying and removing the solvent at low temperature using a reduced pressure drying device to initially form a film.
[0067] 3) The polyamic acid film is heated and imidized in a nitrogen environment to form a polyimide film.
[0068] 4) The curing temperature and time can be optimized according to specific needs, but it is necessary to maintain a low heating rate below 200°C. For example, the heating rate at 80-200°C should be maintained at 2-3°C / min, and the constant temperature time at high temperature of 450°C must be maintained in the range of 25-40min.
[0069] 5) After curing, good adhesion is formed between the polyimide film and the SiOx substrate. A peeling device is needed to slowly peel the PI film from the SiOx substrate. The adhesion between the polyimide film and the substrate can be measured during the peeling process. The peeled film maintains excellent mechanical / optical / thermal properties.
[0070] The following Comparative Examples 1 and 2, as well as Examples 1, 2 and 3 are used to further verify the excellent performance of the polyimide slurry formula and the obtained polyimide film proposed in the present invention.
[0071] At least the following parameters will be tested on the prepared polyimide film:
[0072] Solution viscosity test: The solution viscosity was measured at 25°C using a Brookfield DV-I viscometer.
[0073] Dimensional stability test: The change of film size with temperature was measured by a thermomechanical analyzer (TMA) model TA-Q400. The sample was heated from 0°C to 450°C at a rate of 10°C / min in a nitrogen atmosphere.
[0074] Film forming performance test: observe the state of the polyimide film on the SiOx substrate and its adhesion to the substrate.
[0075] Thermal stability test: The thermal stability of the films was measured by a thermogravimetric analyzer (TGA) model TA-Q50. The samples were heated from room temperature to 800°C at a rate of 20°C / min in a nitrogen atmosphere.
[0076] Mechanical properties test: The mechanical properties of the film samples were measured by INSTRON tensile tester Instron 5969 series. The film samples with a size of 10 μm to 50 μm were stretched at a rate of 10 mm / min at room temperature with an initial length of 100 mm.
[0077] Adhesion test: The film sample was measured by INSTRON tensile tester Instron 5969 series, and the sample width was 20 mm.
[0078] Optical performance test: The optical properties of the film samples were measured by Hunterlab spectrophotometer UltraScanVIS series, with a spectral resolution of 10nm, a grating size of 8nm, and a scanning range of 380-780nm for film samples ranging from 10 microns to 20 microns.
[0079] Comparative Example 1:
[0080] A light yellow polyimide film is prepared from a copolymer of p-phenylenediamine (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA).
[0081] In order to improve the mechanical properties of the film and improve the dimensional stability (reduce CTE), different proportions of anhydride monomers are added for copolymerization, namely, comparative example 1A and comparative example 1B. Its rigid structure can ensure good thermal and mechanical properties.
[0082] PDA / BPDA / PMDA Adhesion Heating conditions unit Molar ratio N / cm 60 to 200°C Comparative Example 1A 100 / 80 / 20 0.03 5℃ / min Comparative Example 1B 100 / 100 / 0 0.04 5℃ / min
[0083] Table 1. Adhesion strength of PDA / BPDA / PMDA copolymers to SiOx inorganic layer
[0084] Table 1 shows the test data of the adhesion between the copolymer formed by two different ratios of anhydride monomers and the SiOx inorganic layer.
[0085]
[0086] Table 2. Properties of PDA / BPDA / PMDA copolymers
[0087] Table 2 shows the performance test data of the copolymers formed by two different ratios of anhydride monomers.
[0088] The following conclusions were drawn based on Comparative Example 1:
[0089] It can be seen from the data in Table 1 that the copolymers of Comparative Example 1A and Comparative Example 1B have too weak adhesion to SiOx and cannot meet the adhesion requirements of the flexible display substrate.
[0090] It can be seen from the data in Table 2 that the performance test data of comparative example 1A, yellowness b* and 1% thermal weight loss Td1%, cannot meet the performance requirements of flexible display, while the performance test of comparative example 1B can meet the performance requirements of flexible display.
[0091] Comparative Example 2:
[0092] A light yellow polyimide film is prepared from a copolymer of p-phenylenediamine (PDA), 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid (DADB), and 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA).
[0093] In order to improve the adhesion between the polyimide film and the SiOx inorganic layer while ensuring the optical / mechanical / thermal properties of the film, different proportions of diamine monomers with carboxyl groups were added for copolymerization to test the adhesion and comprehensive performance of the film.
[0094] PDA / BPDA / PMDA Adhesion Heating conditions unit Molar ratio N / cm 60 to 200°C Comparative Example 2A 75 / 25 / 100 0.51 5℃ / min Comparative Example 2B 85 / 15 / 100 0.46 5℃ / min Comparative Example 2C 95 / 5 / 100 0.38 5℃ / min
[0095] Table 3. Adhesion strength of PDA / DADB / BPDA copolymers to SiOx inorganic layer
[0096] Table 3 shows the test data of the adhesion between the copolymer formed by adding different proportions of diamine monomers with carboxyl groups and the SiOx inorganic layer.
[0097]
[0098]
[0099] Table 4. Properties of PDA / DADB / BPDA copolymers
[0100] Table 4 shows the performance test data of copolymers formed by adding different proportions of diamine monomers with carboxyl groups.
[0101] The following conclusions were drawn based on Comparative Example 2:
[0102] It can be seen from the data in Table 3 that although the adhesion of the copolymers of Comparative Example 2A, Comparative Example 2B and Comparative Example 2C to SiOx does not meet the standard, it has a certain trend as the copolymerization ratio is adjusted.
[0103] It can be seen from the data in Table 4 that the performance test data of comparative example 1A, yellowness b* / total wavelength transmittance Ytotal / tensile strength / thermal performance all failed to meet the standards; the performance tests of comparative examples 2B and 2C can both meet the performance requirements of flexible display materials.
[0104] Embodiment 1:
[0105] A light yellow polyimide film is prepared from p-phenylenediamine (PDA), 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid (DADB), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and a small amount of additive A (silane coupling agent).
[0106] According to the ratio of the above comparative example 2C, a KH series silane coupling agent is added to the polyimide solution at a certain mass concentration to improve the interface energy between the polyimide film layer and the inorganic layer and the wettability of the substrate.
[0107]
[0108]
[0109] Table 5. Adhesion strength of PDA / DADB / BPDA copolymers to SiOx inorganic layer
[0110] Table 5 shows the test data of the adhesion between the copolymers formed by adding different series of silane coupling agents and the SiOx inorganic layer.
[0111]
[0112] Table 6. Properties of PDA / DADB / BPDA copolymers
[0113] Table 6 shows the performance test data of the copolymers formed by adding different series of silane coupling agents.
[0114] The following conclusions were drawn based on Example 1:
[0115] It can be seen from the data in Table 5 that the adhesion of the copolymers of Example 1A and Example 1B to SiOx is greatly improved, while the adhesion of Example 1C, Example 1D, Example 1E, and Example 1F is not improved. Although the coupling agent can effectively improve the wettability of the polymer substrate and improve the interfacial adhesion between the inorganic coating and the substrate, the interaction between the coupling agent and the polymer surface must be considered in the selection of the coupling agent.
[0116] The data in Table 6 only test the performance of Example 1A and Example 1B with higher adhesion. It can be seen from the test results that the yellowness b* value of the performance test data of Example 1A and Example 1B failed to meet the standards; the remaining properties can meet the performance requirements of flexible display materials.
[0117] Embodiment 2:
[0118] A light yellow polyimide film is prepared by adding a small amount of additive A (silane coupling agent) to p-phenylenediamine (PDA), 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid (DADB), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and adjusting the baking conditions (heating rate).
[0119] According to the ratio of Example 1A and Example 1B, the heating rate in the low temperature stage during the high temperature imidization process is adjusted to improve the internal stress in the film layer and enhance the adhesion between the film layer and the SiOx inorganic layer.
[0120]
[0121] Table 7. Adhesion strength of PDA / DADB / BPDA copolymers to SiOx inorganic layer
[0122]
[0123] Table 8. PDA / DADB / BPDA copolymer properties
[0124] Draw the following conclusions based on Example 2:
[0125] It can be seen from the data in Table 7 that by using the copolymers of Example 2A and Example 2B, after adjusting the heating conditions, the heating rate in the range of 60 to 200°C is reduced, the internal stress in the film layer is fully released, and the adhesion to SiOx can be significantly improved. The adhesion of Example 2A and Example 2B has reached the standard.
[0126] It can be seen from the test results in Table 8 that the yellowness b* value of the performance test data of Example 2A and Example 2B still fails to meet the standard; the other properties can meet the performance requirements of flexible display materials.
[0127] Embodiment 3:
[0128] A light yellow polyimide film is prepared by adding p-phenylenediamine (PDA), 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid (DADB), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), adding a small amount of additive A (silane coupling agent), adjusting the baking conditions (heating rate), and adding an appropriate amount of additive B (benzaldehyde).
[0129] According to the ratio and heating conditions of Example 2A and Example 2B, an appropriate amount of benzaldehyde (the molar ratio of diamine) is added to cap the residual diamine end groups in the system, which are then decomposed during the high temperature process and reacted with the dianhydride at the end of the molecular chain in the system, thereby improving the adhesion between the film layer and the SiOx inorganic layer and ensuring the optical properties of the film material.
[0130]
[0131] Table 9. Adhesion strength of PDA / DADB / BPDA copolymers to SiOx inorganic layer
[0132]
[0133] Table 10. PDA / DADB / BPDA copolymer properties
[0134] The following conclusions were drawn based on Example 3:
[0135] It can be seen from the data in Table 9 that by using the copolymers of Example 3A, Example 3B, Example 3C, and Example 3D, after adjusting the heating conditions, the heating rate in the range of 60 to 200°C is reduced, the internal stress in the film layer is fully released, and the adhesion to SiOx can be significantly improved. Adding an appropriate amount of benzaldehyde has no obvious effect on the adhesion. The adhesion of Example 3A, Example 3B, Example 3C, and Example 3D has reached the standard.
[0136] It can be seen from the test results in Table 10 that the yellowness b* value of the performance test data of Example 3B and Example 3D still fails to meet the standard; the performance test data of Example 3A and Example 3C can both meet the performance requirements of flexible display materials.
[0137] It can be seen from the above comparative examples and embodiments that the polyimide slurry for flexible display provided by the present invention that can improve the adhesion with the SiOx inorganic layer and the film prepared therefrom, especially the film materials of Example 3A and Example 3C, are optimized and adjusted by the polymerization monomer and the process, and the addition of the end-capping agent to control the polymerization molecular weight, and by adding a certain amount or proportion of additives A and additives B, while optimizing the process conditions for film heating. Under the condition of ensuring a high adhesion between the film and the SiOx inorganic layer (adhesion greater than 0.8N / cm), the comprehensive performance of the film material can meet the technical requirements of flexible display, strong mechanical properties (modulus greater than 8Gpa, strength greater than 450Mpa), good thermal properties (CTE less than 8ppm / ℃, Tg greater than 450℃, Td1% greater than 560℃), while ensuring good optical properties (b* less than 20, Ytotal greater than 79%).
[0138] The polyimide slurry for flexible display capable of improving adhesion with SiOx inorganic layer and the film prepared therefrom can be used as a substrate material for flexible display and other flexible base materials requiring the same property.
[0139] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A polyimide slurry for a flexible display substrate, characterized in that: The raw materials for preparing the polyimide slurry include diamine, dianhydride, end-capping agent, solvent and additives; The diamine comprises a main monomer and an auxiliary monomer, the main monomer is a diamine monomer containing a carboxyl group, and the molar percentage of the main monomer to the diamine is not more than 30%; The additives include additive A and additive B added in batches, the amount of additive A added is 1-3% of the molar amount of diamine, and the amount of additive B added is 5-50 ppm of the total solution mass; The amount of the end-capping agent added is 0.5-2% of the molar amount of the diamine.
2. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The main monomer in the diamine is 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid.
3. The polyimide slurry for a flexible display substrate according to claim 2, characterized in that: The auxiliary monomer in the diamine is selected from one or more combinations of p-phenylenediamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4-diaminobenzanilide, 4,4'-diaminodicyclohexylmethane, 9,9'-bis(4-amino-phenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 4,4'-diaminodiphenylmethane, 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline], and 4,4-bis(3-aminophenoxy)biphenyl.
4. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The dianhydride is selected from one or more combinations of 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, 4,4-hexafluoroisopropylphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, and bisphenol A diether dianhydride.
5. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The end-capping agent is selected from one or more combinations of maleic anhydride, 4-phenylethynylphthalic anhydride, phthalic anhydride, 4-(phenylethynyl)aniline, 4-aminoacetophenone, 3,3',4,4'-biphenyltetracarboxylic acid, and pyromellitic acid.
6. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The additive A is selected from one or more of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and 3-methacryloyloxypropylmethyldimethoxysilane; the additive B is selected from benzaldehyde.
7. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The amount of the end-capping agent added is preferably 0.5 to 1% of the molar amount of the diamine.
8. The polyimide slurry for a flexible display substrate according to claim 1, characterized in that: The amount of the additive A added is preferably 1.5-2.5% of the molar amount of the diamine, and the amount of the additive B added is preferably 25 ppm of the total solution mass.
9. A method for preparing the polyimide slurry for a flexible display substrate according to any one of claims 1 to 8, characterized in that: The steps include: S1, copolymerizing diamine and dianhydride to generate a polyamic acid solution; S2, adjusting the molar ratio of amine anhydride of the polyamic acid solution obtained in the above step to achieve a suitable viscosity and solid content; S3, adding a specific proportion of the end-capping agent to the polyamic acid solution obtained in the above step; S4, heating the polyamic acid solution obtained in the above step to a specific temperature, slowly adding a certain proportion of additives twice, and repeatedly stirring to ensure that the solution is evenly dispersed; S5. Filter the above-mentioned solution after the polymerization through a filter element with a certain pore size to finally obtain a polyimide slurry.
10. A method for preparing a polyimide film, characterized in that: The steps include: Providing a polyimide slurry prepared by the preparation method according to claim 9; Under room temperature, the coating speed is controlled to uniformly cast the polyimide slurry onto the SiOx substrate; Using a reduced pressure drying device to dry and remove the solvent at low temperature to form a film; The film is heated in a nitrogen environment for imidization to finally form a polyimide film.